ENTERPRENEURIAL-BASED ENGLISH LEARNING (MISS MAYA) TO BUILD ENTREPRENEURIAL LEADERSHIP FOR STUDENTS COLLEGE - Eko Heriyanto; Amin Khudlori (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
The industrial revolution is a fusion of automation technology with cyber. The current trend in the industrial world is starting to touch the virtual world with several systems such as cyber physical systems, internet of things (IoT), cloud computing, and cognitive computing. Revolution 4.0 implements intelligent technology that can be connected to various lines of life, including students’ needs. They must be active to form their entrepreneurial leadership to face these challenges. Absolutely, this must be supported by encouragement, collaboration and integration of learning in the field of entrepreneurship. The purposes of this research are to describe the steps of implementing the Miss Maya, to find and describe the advantages of Miss Maya in building a concrete entrepreneurial leadership, and to determine the effectiveness of Miss Maya in English learning. The method used is mix method; qualitative and quantitative research design. Primary data include references/ literature/ journals/ books related to the discussion. Secondary data include documentation and field data of the implementation obtained through observation and interviews. The results of this research are the implementation of Miss Maya can be done through the preparation, implementation and assessment. Through t-test analysis which showed that sig. (2-tailed) of all = 0.000 and the probability less than 0.05, Miss Maya is an effective strategy to be used in English learning. Miss Maya is a futuristic imaginative integrative English learning method with six main elements of doing business which is expected to be able to foster the students’ entrepreneurial leadership to face the industrial revolution 4.0.